The use of protector to stop transesterification in the synthesis of optimized tri-block coploymer (PCL-co-PLA)-b-PLA-b-(PCL-co-PLA) - Yik, Jia Jun. (2011)
The use of biodegradable polymers in biomedical industries particularly in the area of implant/tissue replacement, tissue engineering and drug delivery has grown significantly. Biodegradable polymers with good elastic and shape recovery properties are need for the biomedical application. Polymer properties are affected by its structure, molar ratio of monomers, molar mass of polymer and the crystalinity of monomers in the polymer. In the review, different polymerization methods for synthesis of biodegradable polymers were discussed. Focus was given to coordinated anionic ring opening polymerization (CAROP) as it allowed large molar mass with random sequencing to be attained. In addition to different polymerization methods, transesterification was also discussed. Transesterification would affect the properties of polymer and determine the sequence of polymerization. Attention was given on ways to suppress transesterification processes during the synthesis of block polymer using tin octate as catalyst. This discovery had lead to a new insight for polymer with L-lactide (L-LA) monomers being polymerized first. In this project, tri-block copolymer, (PCL-co-PLLA)-b-PLLA-b-(PCL-co-PLLA), was synthesized via CAROP with the use of chemical protector, α-methylstyrene. This tri-block copolymer system was assumed to give the best elastic properties. Using design of experiments and mathematical fitting approach of recovery behavior data, polymers with the best shape recovery could be obtained. For a 50 % elongation shape recovery, a tri-block copolymer with fixed middle segment of 5 kDa would have a maximum shape recovery when its soft segment contained 36-44 % of CL with molar mass between 20-30 kDa or when its soft segment contained 44-52 % of CL with molar mass between 10-20 kDa. As for the tri-block copolymer with fixed middle segment of 15 kDa, the maximum shape recovery occurred when its soft segment containing 68-72 % of CL for any molar mass of soft segment.